2021
DOI: 10.1016/j.artd.2021.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of Telehealth Utilization in Hip and Knee Arthroplasty Before and for One Year During the COVID-19 Pandemic

Abstract: Background The Coronavirus Disease 2019 (COVID-19) pandemic has led to an increase in telehealth utilization across healthcare. It is unknown if telehealth use among hip and knee arthroplasty clinics has remained an important healthcare delivery platform. The purpose of the present study was to analyze telehealth utilization prior to and for one-year during the pandemic among four, varied hip and knee arthroplasty clinics. Methods Retrospective data was available from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Orthopedic surgeons became early adopters of telehealth services, with over 80% of orthopedic surgery departments implementing and utilizing these telehealth services ( 20 ), which had previously accounted for less than 1% of all patient visits in the United States pre-pandemic ( 21 ). In a recent study by Bini et al, telehealth services peaked during the height of the early pandemic and were more likely to be utilized for postoperative follow-up visits ( 22 ). The increased utilization of telehealth services for postoperative visits is likely multifactorial and may be explained by its widespread adoption, the sudden ability to receive reimbursement for the telehealth visit, and increased necessity for management of postoperative issues and rehabilitation during a time when social distancing was paramount.…”
Section: Discussionmentioning
confidence: 99%
“…Orthopedic surgeons became early adopters of telehealth services, with over 80% of orthopedic surgery departments implementing and utilizing these telehealth services ( 20 ), which had previously accounted for less than 1% of all patient visits in the United States pre-pandemic ( 21 ). In a recent study by Bini et al, telehealth services peaked during the height of the early pandemic and were more likely to be utilized for postoperative follow-up visits ( 22 ). The increased utilization of telehealth services for postoperative visits is likely multifactorial and may be explained by its widespread adoption, the sudden ability to receive reimbursement for the telehealth visit, and increased necessity for management of postoperative issues and rehabilitation during a time when social distancing was paramount.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the concept of video visits and videoconferencing, expressions such as video consultation and video encounter were used when patients had consultations with health care professionals via a video connection. In addition, telehealth visits [ 72 , 119 ], platforms [ 73 ], eHealth [ 117 ], telephone (or voice) calls [ 45 , 52 , 53 , 63 , 65 , 68 , 73 - 78 , 92 - 98 , 100 , 101 , 118 , 127 , 128 ], text messages [ 90 ], and mobile apps [ 118 ] were mentioned as means for consultation. Looi et al [ 93 , 94 ] found that during the second and third quarters of 2021, the telephone was mostly used for telehealth visits in private psychiatry practice in Australia.…”
Section: Resultsmentioning
confidence: 99%
“…The use of or the possibility for video consultation is especially important for rural and other areas with long distances, though infrastructural or cultural issues may currently prevent or delay the use of digital services in some locations [ 67 , 84 , 108 , 119 ]. According to the results, telephone calls were still used frequently for contacting patients [ 45 , 52 , 53 , 63 , 65 , 68 , 73 , 74 , 92 - 97 , 127 , 128 ]. In some studies, most consultations were done over the phone [ 74 , 93 , 94 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the concept of video visits and videoconferencing, expressions such as video consultation and video encounter were used when patients had consultations with health care professionals via a video connection. In addition, telehealth visits [72,119], platforms [73], eHealth [117], telephone (or voice) calls [45,52,53,63,65,68,[73][74][75][76][77][78][92][93][94][95][96][97][98]100,101,118,127,128], text messages [90], and mobile apps [118] were mentioned as means for consultation. Looi et al [93,94] found that during the second and third quarters of 2021, the telephone was mostly used for telehealth visits in private psychiatry practice in Australia.…”
Section: Use Of Digital Health Servicesmentioning
confidence: 99%